2019
DOI: 10.1016/j.jcjo.2018.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous resolution of euthyroid optic neuropathy

Abstract: Trans-lamina cribrosa pressure difference and open-angle glaucoma. The central India eye and medical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In both cases, vision loss was improved, restoring the initial visual acuity and visual field. In the first case corticosteroid therapy was administered ( 35 ), while the second case was only observed ( 37 ). A conservatory strategy can be rational in cases where disease severity has already peaked and clinical activity score is low; the authors concluded that the spontaneous remission of optic neuropathy can be correlated with normal thyroid function and with the absence of thyroid antibodies ( 37 ).…”
Section: Clinical Characteristics Of Egdmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, vision loss was improved, restoring the initial visual acuity and visual field. In the first case corticosteroid therapy was administered ( 35 ), while the second case was only observed ( 37 ). A conservatory strategy can be rational in cases where disease severity has already peaked and clinical activity score is low; the authors concluded that the spontaneous remission of optic neuropathy can be correlated with normal thyroid function and with the absence of thyroid antibodies ( 37 ).…”
Section: Clinical Characteristics Of Egdmentioning
confidence: 99%
“…The efficiency of pulse corticosteroid treatment is assessed by visual acuity recovery, which was described especially in cases with unilateral involvement ( 36 ). Atypical presentation of euthyroid optic neuropathy with bilateral involvement and severe deterioration in visual acuity revealed a slight amelioration after the intravenous corticosteroid therapy ( 37 ).…”
Section: Treatmentmentioning
confidence: 99%